THE EFFECT OF TRANSFERING ISRAEL CAPITAL CITY TO JERUSALEM TOWARD INDONESIA MACRO ECONOMY - Liliek Nur Sulistiyowati (Ekuitas: Jurnal Ekonomi dan Keuangan, 2020)
United States President Donald Trump has just issued a controversial policy by giving Jerusalem recognition as the capital of Israel. This controversial policy triggered a strong reaction from a number of countries, especially Islamic countries including Indonesia. Indonesia through President Jokowidodo strongly condemned the policy of moving the Israeli capital to Jerusalem because it would disrupt political and security stability in the Middle East region. In the midst of the political impact caused by President Donald Trump's policies also affected the global economy. The world stock exchanges reacted immediately with the existence of these policies, one of which was the fall of the stock market index in Japan and South Korea due to investor concerns.